A study of anti-poly (ADP-ribose) antibodies and an anti-DNA antibody idiotype and other immunological abnormalities in lupus family members. Issue 6 (June 1986) - Dudeney, C; Shoenfeld, Y; Rauch, J; Jones, M; Mackworth Young, C; Tavassoli, M; Shall, S; Isenberg, D A
Abstract : The genetic background of systemic lupus erythematosus (SLE) has been reexamined in a study of the serum of 31 lupus patients and 80 asymptomatic first degree relatives by measuring a common, cross reacting anti-DNA antibody idiotype designated 134, antibodies to poly(ADP-ribose), serum C3, circulating immune complexes, and antinuclear antibodies (ANA). Over 30% of the relatives had raised 134 and anti-poly(ADP-ribose) levels, and 9% had ANA titres greater than 1/20. In contrast, only one relative had a low serum C3 level. These results confirm that immunogenetic abnormalities associated with the production of autoantibodies and particular idiotypes must exist amongst lupus relatives as well as the patients. The production of autoantibodies, however, is not necessarily matched to the clinical expression of SLE.